The impact of physical functions on depressive symptoms in people with multiple sclerosis - Carlos Bernardo TAUIL; Cintia RAMARI; Flávia Martins DA SILVA; Erica BRASIL; Ana de DAVID; Jaqueline Ramos Andrade GOMES; Felipe von Glehn SILVA; Carlos Otávio BRANDÃO; Leonilda Maria Barbosa DOS SANTOS; Leopoldo dos SANTOS-NETO (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Multiple sclerosis (MS) is an immune-mediated disease that affects the central nervous system. The impact of MS transcends physical functions and extends to psychological impairment. Approximately 50% of people with MS develop depressive symptoms during their lifetime and depressive symptoms may predict impairment of physical functions. However, prediction of depressive symptoms based on objective measures of physical functions is still necessary. Objective: To compare physical functions between people with MS presenting depressive symptoms or not and to identify predictors of depressive symptoms using objective measures of physical functions. Methods: Cross-sectional study including 26 people with MS. Anxiety and/or depressive symptoms were assessed by the Beck Depression Inventory-II (BDI-II) and by the Hospital Anxiety and Depression Scale (HADS). Outcomes of physical functions included: the Nnnine-hole Ppeg Ttest (NHPT), knee muscle strength, balance control, the Timed Up and Go Test (TUG), and the 6-minute walk test (6MWT). Perceived exertion was measured using the Borg scale. Results: The frequency of depressive symptoms was 42% in people with MS. Balance control during a more challenging task was impaired in people with MS who presented depressive symptoms. Balance could explain 21-24% of the variance in depressive symptoms. 6MWT and TUG presented a trend of significance explaining 16% of the variance in the BDI-II score. Conclusions: Impairment in physical functions consists in a potential predictor of depressive symptoms in people with MS. Exercise interventions aiming at the improvement of physical functions, together with the treatment of depressive symptoms and conventional medical treatment, are suggested.